Revisiting the Overlooked Infection: Rickettsioses - Khie Chen Lie; Erni Juwita Nelwan; Adeline Pasaribu; Sharifah Shakinah; Robert Sinto; Leonard Nainggolan (Interna Publishing, 2022)
The prevalence of human Rickettsioses cases in Indonesia is unknown and could probably be underestimated. The high prevalence of seropositive Rickettsia sp. was reported in small mammals (as vectors) and humans. In Indonesia, a recent study in patients with acute fever revealed that the prevalence of Rickettsioses is 10%. Many cases of Rickettsioses were often misdiagnosed with dengue fever, enteric fever, or leptospirosis due to their overlapping clinical manifestation. The limitation of point of care testing in Indonesia hindered the adequacy of diagnosis confirmation. Appropriate empirical or definitive treatment with macrolide, mainly doxycycline, is preferable compared to other broad-spectrum antibiotics, such as cephalosporin or quinolones. Moreover, when left untreated, Rickettsioses may deteriorate progressively to fatal outcomes, such as meningitis, sepsis, and even death. The awareness of health care practitioners, the availability of confirmatory rapid diagnostic tests and adequate treatment choices are important in eradicating this disease.